Determinants of Indonesia’s Environmental Quality Index, Including Human Development, Economic Growth, Deforestation, and Budget Allocation - Rajib Wahyu Nugroho; Maryono; Jafron Wasiq Hidayat (CV. Literasi Indonesia, 2025)
Environmental quality in Indonesia remains under sustained pressure due to ongoing deforestation, resource-intensive economic growth, and persistent regional development disparities. This study analyzes the influence of the Human Development Index (HDI), Gross Regional Domestic Product (GRDP), deforestation, and regional government revenue and expenditure budgets on the Environmental Quality Index (EQI) across 33 Indonesian provinces. The analysis employs panel data regression, with a Fixed Effects Model selected based on the Hausman specification test. The results reveal that HDI exerts a positive and statistically significant effect on environmental quality, with a one-point increase in HDI corresponding to a 1.988-point rise in the EQI. Deforestation and regional government budget variables do not demonstrate statistically significant effects on the EQI. These findings suggest that higher levels of human development are associated with improved environmental conditions, whereas economic growth trajectories that are predominantly driven by natural resource exploitation continue to degrade environmental quality. Accordingly, regional development policies should be directed toward strengthening human development performance, integrating environmental considerations into economic growth processes, and enhancing the effectiveness of regional budget allocations for environmental sustainability, in order to achieve inclusive and sustainable development.